Assessing Challenges and Sources of Dissatisfaction among Accredited Social Health Activists Employees - Abrar, Deeba; Malik, Azam (International Review of Management and Marketing, 2024)
Accredited Social Health Activists (ASHAs) are integral to India’s healthcare system, particularly in rural and underserved areas like those in district Aligarh, Uttar Pradesh. They serve as community health workers who facilitate access to essential health services, but their roles often place them in vulnerable positions. Operating within patriarchal societies and situated at the lower levels of the healthcare hierarchy, ASHAs are prone to various forms of violence and harassment. Despite their crucial role, there is limited understanding of the specific challenges they face, particularly regarding harassment in their work environment. This study aims to identify the key challenges encountered by ASHA workers in the Aligarh district of Uttar Pradesh and sources of dissatisfaction faced by ASHAs. A cross-sectional survey was conducted involving a representative sample 150 of ASHAs across several blocks of in Aligarh of Uttar Pradesh. Data were collected through structured questionnaires and semi-structured interviews. The survey addressed various aspects, including working conditions, support from healthcare systems, remuneration, training, and community relations. In a study of 150 ASHA workers, key challenges include delays in incentives (70%), excessive workload (92%), and unsatisfactory training (71.3%). Many faces harsh working conditions (73.3%), harassment (95.3%), and high stress (89.3%). Issues like inadequate facilities (97%) and transportation difficulties (90.6%) further impact their performance and well-being. This study evaluates ASHA workers’ duties, challenges, and well-being. Despite their critical role, they face financial instability, inadequate facilities, harsh conditions, and harassment, including from hospital staff. Long travel, stigma, and social discrimination further impact their effectiveness and morale, emphasizing the need for better support and protective measures.